Barriers of Good Glycemic Control Of Known Diabetic Patients in a Tertiary Care Hospital - Islam, Md Maidul; Islam, Md Khairul; Jahan, Farjana; Gomes, Lilian Catherene; Hossain, fahima Sharmin; Hossain, Mohammad Murad (Journal of Dhaka Medical College, 2023)
Introduction: uncontrolled Diabetes mellitus is a growing cause of disability and premature death. HbA1C is an indicator of glycemic control status over the previous three months. Therefore, to minimize the morbidity and mortality of diabetic patients, it would be necessary to identify the factors associated with poor glycemic control, which may not be similar to developed countries. Objective: To identify factors acting as a barrier to reasonable glycemic control of known diabetic patients in Bangladesh Materials and methods: This is a hospital-based descriptive cross-sectional study among diabetic patients with poor glycemic control in the indoor and outdoor Medicine and Endocrinology departments of Dhaka medical college hospital, Dhaka, from July 2019 to December 2019 (6 months). For at least three months, patients who had uncontrolled Diabetes were selected by purposive and convenient sampling method. Results: One hundred and six patients with poor glycemic status were included in the analysis. Aged persons were at risk for poor glycemic control, especially age range of 50-69 years (65.0%) P-value was .004. Duration of Diabetes and educational status were significantly associated with poor glycemic control. P values were 0.001 and .003, respectively. Conclusion: Patient education plays a pivotal role in controlling glycemic control, favoring treatment success, reducing adverse drug events, and preventing further complications of Diabetes. J Dhaka Med Coll. 2022; 31(1) : 9-14